2007
DOI: 10.1037/0021-843x.116.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Impaired specific autobiographical memory as a risk factor for posttraumatic stress after trauma.

Abstract: This study tested the proposal that impaired retrieval of specific autobiographical memories is a risk factor for psychological disturbance after trauma exposure. Trainee firefighters (N = 60) were assessed during training (before trauma exposure) on the Autobiographical Memory Test, Clinician Administered PTSD Scale, Beck Depression Inventory (BDI-II), and Traumatic Events Questionnaire. Participants were reassessed 4 years later (N = 46) on the Posttraumatic Diagnostic Scale and BDI-II. All participants had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 47 publications
8
80
0
2
Order By: Relevance
“…(2000) reported that almost 22 out of 325 retired as a consequence of mental stress. The psychological cost of this exposure increases the risk of long-term problems such as PTSD symptoms (Al-Naser & Everly, 1999;Bryant, Sutherland, & Guthrie, 2007;Corneil, Beaton, Murphy, Johnson, & Pike, 1999;Mitani, Fujita, Nakata, & Shirakawa, 2006) as well as depression and anxiety (Carey, Al-Zaiti, Dean, Sessanna, & Finnell, 2011;Chen et al, 2007;Markus Heinrichs et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…(2000) reported that almost 22 out of 325 retired as a consequence of mental stress. The psychological cost of this exposure increases the risk of long-term problems such as PTSD symptoms (Al-Naser & Everly, 1999;Bryant, Sutherland, & Guthrie, 2007;Corneil, Beaton, Murphy, Johnson, & Pike, 1999;Mitani, Fujita, Nakata, & Shirakawa, 2006) as well as depression and anxiety (Carey, Al-Zaiti, Dean, Sessanna, & Finnell, 2011;Chen et al, 2007;Markus Heinrichs et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…However, laboratory word tasks are not necessarily an ecologically valid measure of real-life memories of one's personal past, defined as autobiographical memory (Tulving, 2002). Furthermore, disorders such as acute stress disorder, depression, or post traumatic stress disorder (PTSD) that are characterised by cortisol disregulations have been related to recall of nonspecific, over-general autobiographic memories (e.g., Bryant, Sutherland, & Guthrie, 2007;Harvey, Bryant, & Dang, 1998;Kangas, Henry, & Bryant, 2005;Williams & Scott, 1988).…”
mentioning
confidence: 99%
“…In general, findings indicate that preexposure tendencies for overgeneral mem-ory are associated with increased risk of PTSD. For example, Bryant, Sutherland, and Guthrie ( 14 ) found that impaired retrieval of specific memories in response to positive cues prior to trauma exposure among trainee firefighters predicted posttraumatic stress symptom severity after trauma exposure, a finding consistent with the cross-sectional literature. Harvey and Bryant ( 46 ) likewise found that overgeneral retrieval of autobiographical memories shortly after motor vehicle accident exposure predicted subsequent PTSD.…”
Section: Alterations In Autobiographical Memory: Predisposition Ormentioning
confidence: 80%
“…In another study, the difficulty in retrieving specific memories among war veterans with PTSD was particularly pronounced in those individuals wearing military regalia ( 10 ) ; these individuals also retrieved a disproportionate number of war-related memories, a finding that was interpreted as reflecting the centrality of their war experience to their sense of self. One explanation of these findings is that impoverished recall of positive memories reflects a problem among PTSD-diagnosed trauma survivors in accessing the emotionally positive aspects of their histories and identities ( 10,11,14 ) . In keeping with this formulation, when asked to produce self-defining memories, PTSD-diagnosed trauma survivors, as compared to non-PTSD-diagnosed trauma survivors and nonexposed controls, reported more self-defining memories that were trauma related and of negative valence ( 15 ) .…”
Section: Overgeneral Nature Of Autobiographical Memorymentioning
confidence: 91%
See 1 more Smart Citation